2019
DOI: 10.3389/fphys.2018.01897
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Association Between the rs1138272 Polymorphism of the GSTP1 Gene and Cancer Susceptibility

Abstract: Background: We obtained conflicting results regarding the relationship between the genetic role of the rs1138272 C/T polymorphism of the GSTP1 (Glutathione S-Transferase pi) gene and the risk of various cancers.Methods: Using the presently available data, a meta-analysis was conducted to comprehensively evaluate the genetic relationship between the GSTP1 rs1138272 polymorphism and cancer susceptibility.Results: A total of 43 studies including 15,688 cases and 17,143 controls were recruited into our quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In addition, a meta-analysis conducted in 2013 in an Asian population, which included 28 case control studies, revealed that GSTP1-rs1138272 was associated with an increased risk of lung cancer [28]. Another meta-analysis included 43 studies with more than 15,000 cases and more than 17,000 controls, revealed that the GSTP1-rs1138272 (TT) genotype was more likely to be associated with cancers in Asian and African populations [29]. While the GSTP1-rs1138272 (CT) genotype was possibly related to lung cancer susceptibility in Caucasians [29].…”
Section: Gstp1-rs1695mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a meta-analysis conducted in 2013 in an Asian population, which included 28 case control studies, revealed that GSTP1-rs1138272 was associated with an increased risk of lung cancer [28]. Another meta-analysis included 43 studies with more than 15,000 cases and more than 17,000 controls, revealed that the GSTP1-rs1138272 (TT) genotype was more likely to be associated with cancers in Asian and African populations [29]. While the GSTP1-rs1138272 (CT) genotype was possibly related to lung cancer susceptibility in Caucasians [29].…”
Section: Gstp1-rs1695mentioning
confidence: 99%
“…Another meta-analysis included 43 studies with more than 15,000 cases and more than 17,000 controls, revealed that the GSTP1-rs1138272 (TT) genotype was more likely to be associated with cancers in Asian and African populations [29]. While the GSTP1-rs1138272 (CT) genotype was possibly related to lung cancer susceptibility in Caucasians [29]. No significant association between the GSTP1-rs1695: rs1138272 combinations (AA:CC), (GG:CC) and (GG:TT) and the risk of lung cancer was found in a Finnish population [30].…”
Section: Gstp1-rs1695mentioning
confidence: 99%
“…However, since this SNP is located in the ARE-like motif of the gene, importance for self-induction of the Nrf2 is being emphasized throughout the literature [ 26 , 28 , 29 ]. In the case of GSTP1 gene polymorphisms, two most commonly occurring SNPs are rs1695 and rs1138272 [ 30 ]. Substitution of A313G in the case of rs1695 causes change of isoleucine with valine at position 105 (Ile105Val) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There exist a group of genes, such as the Glutathione S-transferase alpha 1 (GSTA1), Glutathione S-transferase theta 1 (GSTT1), Glutathione S-Transferase pi (GSTP1), Glutathione S-transferase Mu1 (GSTM1) and Glutathione S-transferase Mu3 (GSTM3), in the GSTs supergene family [4,5]. In addition, several variants, such as present/null of GSTM1 or GSTT1 gene, rs1695, rs1138272 of GSTP1 gene, rs1799735 of GSTM3, were observed [6,7]. A deletion of three base pairs-induced GSTM3 rs1799735, also known as GSTM3 A/B or AGG/del, is situated in the intron 6 of the GSTM3 gene [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The variants with in the above GST family genes were reported to be associated with the genetic susceptibility to some clinical cancer diseases [6,7,11,12]. For example, GSTP1 rs1138272 polymorphism may be linked to the risk of overall cancer in the Asian and African populations.…”
Section: Introductionmentioning
confidence: 99%